Properties Of Biocompatible Mg-Zn Alloy Based Hybrid Composite Fabricated By Powder Metallurgy - Ab Rashid, Nazirah (2020)
In this study, biodegradable and biactive metallic material of magnesium-zinc/hydroxyapatite/alumina (Mg-Zn/HAP/Al2O3) hybrid composite fabricated by powder metallurgy was developed. The main objective of this work was to investigate the effects of HAP and Al2O3 amount of content and weight ratio on mechanical, corrosion and wear behaviour of Mg-Zn based alloy. The powders of Mg, Zn, HAP and Al2O3 were mixed in a high energy ball mill, compacted under 400 MPa and sintered at 300˚C. The increasing Al2O3 content from 0 to 15 wt. % in the hybrid composite resulted in improvement in hardness (57.60 Hv to 83.87 Hv) and compression strength (126.48 MPa to 244.20 MPa). Based on polarization test, 0 wt. % Al2O3 composite (i.e. consist of 15 wt. % HAP) is the most noble with corrosion potential (-1.604 V) and the lowest current density and corrosion rate (0.252 μA/cm2, 1.25 mm/year, respectively) due to apatite formation in Hanks Balanced Salt Solution (HBSS). While 5 wt. % Al2O3 (i.e. with 10 wt. % HAP) shows the highest wear resistance due to high hardness of Al2O3. Composite with 20 wt. % ceramic (HAP and Al2O3 with 2:1weight ratio) exhibited low hardness (67.03 Hv), low compressive strength (138.67 MPa), high corrosion rate (2.34 mm/year) and the low volume loss due to wear (4.9 to 14.6 x 10-4 mm3). Overall, hybrid composite with addition of 5 wt.% Al2O3 and 10 wt. % HAP at weight ratio 2:1 displayed the best properties, for biomedical implant application.